From the gardens of Smyrna to the slums of Thessaloniki – cultural and social aspects of the integration of prosfyges into Greek society - Czekalski, Tadeusz (Balcanica Posnaniensia. Acta et studia, 2009)
The article addresses the cultural and social aspects of the integration of Greek refugees from Asia Minor into Greek society after the defeat of the Greek army in the war with Turkey in 1922. The author draws on the literature on the subject, demographic statistics, administrative documents and memoirs, as well as research on the collective memory of refugees. The conclusions indicate that the integration process was lengthy, fraught with tension and mutual prejudice. The ‘old’ Greeks perceived the refugees as culturally alien due to their language, customs and Turkish-sounding surnames. The prosfyges, with their strong sense of religious identity, formed their own parish communities and organisations. On the other hand, their presence led to a re-evaluation of Greek national identity, which became increasingly rooted in the Orthodox tradition. Ultimately, the experience of the prosfyges, initially marked by isolation and conflict, became an important element of Greek historical memory and national identity, revealing the complexity of adaptation and cultural processes in conditions of forced migration.